Optimalisasi Penggunaan Lahan dengan Sistem Agroforestri di Desa Ngancar, Ngawi: Land Use Optimization using Agroforestry System in Ngancar Village, Ngawi - Winastuti Dwi Atmanto; Priyono Suryanto; Adriana Adriana; Ananto Triyogo; Eny Faridah; Daryono Prehaten; Budiadi Budiadi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Most of the people live in Ngancar village, Pitu sub-district, Ngawi  district, East Java  are farmers. They cultivate crops not only on their privately-owned land but also on Perhutani’s forest land which is dominated by old teak stands. One of the problem in cultivating agricultural crops under old teak stands is the crown cover. It will significantly reduce the light intensity received by crops, and consequently decreasing the yield potential. Knowledge about the shade tolerant species and various silvicultural techniques should be understood and practiced by farmers, so that they can optimize the land use and achieve the high yield. Community service activities by Team of Silviculture Department, Faculty of Forestry UGM are carried out by establishing demonstration plot, maintenance, evaluation of plant growth and health, as well as problem identification and evaluation of successful cultivation under agroforestry system. Observation, focus group discussion, interview, questionnaire and counselling are implemented in order to collect related data and information. This community service activity uses descriptive qualitative approach. Outcome from this community service activity is recommendation of several shade tolerant species which can be cultivated under the old stands such as longan, avocado, and ginger. In addition, silvicultural treatment such as embroidery, weeding, and pest and disease control should be intensively managed  in agroforestry practice in order to achieve optimal yield productivity.